Peran Literasi Digital Pada Siswa Sekolah Dasar Untuk Pencapaian Sustainable Development Goals (SDGs) 2030 - Devi Widiyantti; Dinda Fadila; Nita Pratiwi; Ichsan Fauzi Rachman (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study analyzes the importance of digital literacy education in elementary school students in the context of achieving the 2030 Sustainable Development Goals (SDGs). The research method used is a literature review study. The results show that digital literacy education in elementary school students has an important role in preparing them to face challenges and opportunities in the digital era, and contributes significantly to the achievement of SDGs 2030. This research also identifies strategies that can be applied in digital literacy education for elementary school students to support the achievement of SDGS 2030.